Waterproof impervious concrete as well as preparation method and application thereof

By adding specific components to the concrete, such as iron tailings ash, nano-hydrated calcium silicate gel and ternary expanded crack-resistant fibers, the concrete's seepage resistance is significantly improved, and the problem of concrete leakage protection in high-pressure environments is solved, and the safety of the project and the water storage capacity of the pool are improved.

CN119750989APending Publication Date: 2025-04-04NO 1 CONSTR ENG CO LTD OF CHINA CONSTR THIRD ENG BUREAU CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411956323.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-28
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

In high-pressure and strong environments, the self-waterproofing performance of concrete cannot meet the requirements of anti-leakage, which affects the safety of the pool structure and water storage capacity.

Method used

A waterproof and anti-seepage concrete is used, and its components include cement, sand, gravel, fly ash, iron tailings ash, ore powder, water reducing agent, ternary expansion crack-resistant fiber and nano-hydrated calcium silicate gel. Through the combination of these components, the concrete's anti-seepage performance is significantly improved and the probability of shrinkage cracks is reduced.

Benefits of technology

It greatly improves the seepage resistance of concrete, reduces the probability of shrinkage cracks in concrete, effectively solves the problem of anti-seepage in high water pressure environments, and improves the safety of the project and the water storage capacity of the pool.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005215939240000081
    Figure BDA0005215939240000081
Patent Text Reader

Abstract

The invention provides waterproof impervious concrete as well as a preparation method and application thereof. The waterproof impervious concrete is prepared from the following components: 240 to 300kg of cement, 680 to 850kg of sand, 950 to 110kg of broken stone, 55 to 70kg of fly ash, 72 to 90kg of iron tailing ash, 55 to 70kg of mineral powder, 5 to 6.5 kg of water reducing agent, 18 to 23kg of ternary expansion anti-cracking fiber, 30 to 42kg of nano calcium silicate hydrate gel and 150 to 185 kg of water in each cubic meter of concrete. By doping the nano calcium silicate hydrate gel and the ternary expansion anti-cracking fiber, the porosity of the concrete can be remarkably reduced, and the anti-cracking and anti-seepage performance of the concrete is optimized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of concrete preparation, and in particular to waterproof and anti-seepage concrete and a preparation method and application thereof. Background Art

[0002] When faced with engineering projects involving major risks, such as ultra-high water pools, after the construction is completed and the water inside the pool reaches a high water level, the huge water pressure poses a severe test to the pool structure, and the risk of concrete wall penetration is greatly increased, which has a great negative impact on the safety of the project and the water storage capacity of the pool.

[0003] At present, relying solely on the self-waterproofing of concrete can no longer meet the requirements of leakage under high pressure and strong environment, and some admixtures must be used to improve the anti-seepage performance of concrete.

[0004] Therefore, there is an urgent need to develop a waterproof and anti-seepage concrete that can adapt to high pressure and strong environment. Summary of the invention

[0005] In order to solve the problem that the self-waterproofing of concrete cannot meet the anti-leakage requirements under the high pressure environment mentioned above, the present invention proposes a waterproof and anti-seepage concrete and a preparation method thereof, which greatly improves the anti-seepage performance of concrete, greatly reduces the probability of shrinkage cracks in concrete, and solves the anti-leakage problem under high water pressure environment.

[0006] In order to achieve the above object, the present invention adopts the following technical scheme.

[0007] The present invention proposes a waterproof and anti-seepage concrete, comprising the following components: cement 240-300kg / m 3 , Sand 680-850kg / m 3 , Crushed stone 950-1170kg / m 3 、Fly ash 55-70kg / m 3 、Iron tailings ash 72-90kg / m 3 、Mineral powder 55-70kg / m 3 , water reducing agent 5-6.5kg / m 3 , ternary expansion anti-cracking fiber 0.8-1.0kg / m 3 , Nano hydrated calcium silicate gel 30-42kg / m 3 and water 150-185kg / m 3 .

[0008] Furthermore, the water reducing agent is a polycarboxylic acid high performance water reducing agent.

[0009] Furthermore, in the above waterproof and impermeable concrete, the concrete includes the following components: cement 271kg / m 3 , sand 760kg / m3 、Crushed stone 1056kg / m 3 、Fly ash 62.5kg / m 3 、Iron tailings ash 81kg / m 3 、Mineral powder 62.5kg / m 3 , water reducing agent 5.8kg / m 3 , ternary expansion anti-cracking fiber 0.9kg / m 3 , Nano hydrated calcium silicate gel 36kg / m 3 、Water 166.7kg / m 3 .

[0010] Furthermore, in the above waterproof and anti-seepage concrete, the cement is P·O42.5 silicate cement; the particle size of the sand is 0.25-0.5 mm, and the mud content is less than or equal to 3%; and the particle size of the crushed stone is 5-25 mm.

[0011] Furthermore, in the above-mentioned waterproof and anti-seepage concrete, the fly ash is of grade II, with a fineness of less than 25%, a loss on ignition of less than 8%, and a water demand ratio of less than 105%.

[0012] Furthermore, in the above-mentioned waterproof and anti-seepage concrete, the main components of the iron tailings ash include SiO2, Fe2O3, Al2O3, CaO, MgO, and Na2O.

[0013] Furthermore, in the above-mentioned waterproof and anti-seepage concrete, the ternary expansion anti-cracking fiber is a steel-PVA-polypropylene ternary mixed fiber, and the mixing ratio is 1:0.7:1.

[0014] Furthermore, in the above-mentioned waterproof and anti-seepage concrete, the mineral powder is S95 grade mineral powder.

[0015] On the other hand, the present invention also provides a method for preparing concrete, comprising the following steps:

[0016] First, sand, gravel, cement, fly ash, iron tailings ash and mineral powder are put into the mixer in sequence and mixed for a first preset time. Then, water reducer, ternary expansion anti-cracking fiber and nano-hydrated calcium silicate gel are added and mixed with water for a second preset time. Finally, the remaining mixing water is added and mixed for a third preset time to obtain concrete.

[0017] Furthermore, in the above preparation method, in the stirring step, the sum of the three preset time lengths should be less than or equal to 270 seconds.

[0018] On the other hand, the present invention also proposes an application of concrete, comprising the following steps:

[0019] Transportation step: transporting the waterproof and anti-seepage concrete obtained through the above steps to the pouring site for concrete spreading and pouring;

[0020] Casting and vibrating steps: the concrete wall is cast by the inclined layered casting method, and a vibrating rod is used for vibrating. When using the vibrating rod, it should be straight up and down, inserted quickly and pulled out slowly, and attention should be paid to the position of the steel cage;

[0021] Curing step: performing thermal insulation curing on the concrete in a closed form.

[0022] Furthermore, the curing period is 14 days.

[0023] Furthermore, in the above application, in the transportation step, the residence time of the concrete is less than or equal to 45 minutes, the slump loss is less than or equal to 10%, and the total pouring time is less than or equal to 6 hours.

[0024] Compared with the prior art, the advantages of the present invention are as follows:

[0025] 1) Adding iron tailings ash, the substance produced by the chemical reaction between iron tailings ash and calcium hydroxide produced by cement hydration fills the voids in the concrete, which gradually reduces the porosity inside the concrete; at the same time, the iron tailings ash has a good gradation, and the iron tailings ash that has not undergone chemical reaction will also fill the voids in the concrete, thereby reducing the porosity of the concrete and improving the impermeability of the concrete. At the same time, the iron tailings ash can complement the fly ash, and the two work together to increase the impermeability and corrosion resistance of the concrete.

[0026] 2) Doped with nano-hydrated calcium silicate gel. Nano-hydrated calcium silicate gel has the advantages of small particle size, good dispersion effect, and obvious nucleation and filling effect. It can significantly accelerate the growth of hydration products in the pore space of cement concrete, reduce porosity, and improve the early strength of cement-based materials. At the same time, the excess calcium ions in the gel can be used as a compensator to promote crack healing and improve impermeability and environmental resistance. Calcium carbonate slowly dissolves and combines with calcium ions to form crystals, further reducing the porosity of concrete.

[0027] 3) The doped ternary expansion anti-cracking fiber and the steel-PVA-polypropylene ternary hybrid fiber work together to significantly inhibit tiny pores. Under load, the fiber can more effectively reduce the porosity and pore size of concrete and improve the compactness of concrete. At the same time, the three-dimensional spatial grid structure formed by the steel-PVA-polypropylene ternary hybrid fiber enables the fibers to produce a synergistic effect, more effectively inhibiting the generation and development of pores with different pore sizes at different load stages, and improving the crack resistance and impermeability of concrete under various load levels. DETAILED DESCRIPTION

[0028] Exemplary embodiments of the present invention will be described in more detail below. The following embodiments only show exemplary embodiments of the present invention, and the present invention can be implemented in various forms and should not be limited by the embodiments set forth herein. On the contrary, these embodiments are provided in order to enable a more thorough understanding of the present invention and to enable the scope of the present invention to be fully communicated to those skilled in the art. It should be noted that, in the absence of conflict, the embodiments of the present invention and the features described in the embodiments can be combined with each other. The present invention will be described in detail below in conjunction with the embodiments.

[0029] The present invention proposes a waterproof and anti-seepage concrete, comprising the following components: cement 240-300kg / m 3 , Sand 680-850kg / m 3 , Crushed stone 950-1170kg / m 3 、Fly ash 55-70kg / m 3 、Iron tailings ash 72-90kg / m 3 、Mineral powder 55-70kg / m 3 , Polycarboxylic acid high performance water reducing agent 5-6.5kg / m 3 , ternary expansion anti-cracking fiber 0.8-1.0kg / m 3 , Nano hydrated calcium silicate gel 30-42kg / m 3 , Water 150-185kg / m 3 .

[0030] Preferably, the concrete comprises the following components: cement 271kg / m 3 , sand 760kg / m 3 、Crushed stone 1056kg / m 3 、Fly ash 62.5kg / m 3 、Iron tailings ash 81kg / m 3 、Mineral powder 62.5kg / m 3 , polycarboxylic acid high performance water reducing agent 5.8kg / m 3 , ternary expansion anti-cracking fiber 0.9kg / m 3 , Nano hydrated calcium silicate gel 36kg / m 3 、Water 166.7kg / m 3 .

[0031] The cement is P·O42.5 silicate cement.

[0032] Preferably, the polycarboxylic acid high performance water reducer is S95 polycarboxylic acid high performance polycarboxylic acid high performance water reducer.

[0033] Preferably, the sand is ordinary river sand with a particle size of 0.25 to 0.5 mm and a mud content of less than or equal to 3%.

[0034] Preferably, the particle size of the sand is 0.25 to 3 mm, preferably 0.25 to 0.5 mm; the crushed stone is a secondary graded crushed stone, and the particle size of the crushed stone is 5 to 25 mm, preferably 5 to 10 mm.

[0035] The fly ash is of grade II, with a fineness of less than 25%, a loss on ignition of less than 8%, and a water requirement ratio of less than 105%. In this embodiment, in order to physically disperse the cement particles and make the distribution of cement more uniform, a certain proportion of fly ash needs to be added. Due to the slow hydration of fly ash, when the water-cement ratio of concrete is low, fly ash can make the cement hydrate more fully; fly ash can also slow down the hydration rate, so that the temperature change caused by the hydration of concrete is reduced, which can well prevent the concrete from generating temperature cracks. In addition, the bulk density of fly ash is only about 2 / 3 of that of cement, and good quality fly ash contains a large amount of glass microbeads, which makes the fly ash have a better particle shape, so it can more densely fill the gaps of aggregate particles and wrap them to form a lubricating layer. This effect is more significant for concrete with less cement; finally, fly ash reacts with CA(OH)2 crystals enriched around aggregate particles to generate products with cementitious properties, strengthen the weak transition zone, and significantly improve the various properties of concrete. The aggregate particles in this embodiment refer to sand and gravel.

[0036] The main components of the iron tailings ash are SiO2, Fe2O3, Al2O3, CaO, MgO, and Na2O, and the particle size and proportion are as follows: 0.025±0.005mm / 5%, 0.035±0.005mm / 10%, 0.050±0.010mm / 25%, 0.075±0.015mm / 50%, and 0.095±0.005mm / 10%. The substances produced by the chemical reaction between the iron tailings ash and the calcium hydroxide produced by cement hydration are filled in the concrete voids, so that the porosity inside the concrete gradually decreases; the iron tailings ash has a good gradation, and the iron tailings ash that has not undergone chemical reaction will also be filled in the concrete voids, thereby reducing the porosity of the concrete and improving the impermeability of the concrete. At the same time, the iron tailings ash can complement the fly ash, and the two work together to increase the impermeability and corrosion resistance of the concrete.

[0037] The nanometer calcium silicate hydrate gel is mainly prepared by stirring calcium oxide, calcium carbonate and quartz powder with water, maintaining a constant temperature, and stirring and reacting in a hydrothermal reactor.

[0038] The constant temperature was 180° C. The reaction was carried out in a hydrothermal reactor at a stirring speed of 250 rpm for 1.5 hours.

[0039] Among them, calcium oxide, calcium carbonate and quartz powder are prepared according to the mass ratio of 196:4:375. The water-solid ratio (mass ratio) is 10:1. The nano-hydrated calcium silicate gel particles prepared by the present invention generally have a particle size of 10 to 20 μm, and have the advantages of small particle size, good dispersion effect, and obvious crystal nucleus and filling effect. It can significantly accelerate the growth of hydration products in the pore space of cement concrete, reduce porosity, and improve the early strength of cement-based materials; at the same time, the excess calcium ions in the gel can be used as a compensator to promote crack healing and improve impermeability and environmental resistance; the overall proportion of calcium carbonate in the raw materials is not high, and its main function is to stabilize the reaction process. Its slow dissolution and crystallization generated by combining with calcium ions can also further reduce the porosity of concrete.

[0040] The ternary expansion anti-cracking fiber is preferably a steel-PVA-polypropylene ternary hybrid fiber, and is further preferably a steel-PVA-(PH-A modified polypropylene anti-cracking) fiber. The main function of the steel fiber is to inhibit the generation and expansion of cracks, the main function of PVA is to improve the durability and crack toughness of concrete, the main function of the polypropylene fiber is to improve the anti-permeability of concrete, and the PH-A modified polypropylene anti-cracking fiber has better anti-permeability than ordinary polypropylene anti-cracking fiber. Compared with single mixing, the three-fiber composite mixing can complement each other in performance and play a positive mixing effect. The three-dimensional space grid structure formed makes the fibers produce synergistic effects, more effectively inhibiting the generation and development of pores with different pore sizes at different load stages, and improving the crack resistance and anti-permeability of concrete at various load levels.

[0041] The grade of the mineral powder can be S75, S95, S105 or S115. In this embodiment, S95 grade slag powder is preferred. Mineral powder has micro-aggregate effect, micro-nucleus effect and volcanic ash effect in concrete, and can also improve the impermeability of concrete, reduce hydration heat, and prevent temperature cracks. Therefore, mineral powder used as an admixture for concrete can significantly improve or enhance the comprehensive performance of concrete.

[0042] In the concrete prepared by the above formula in the embodiment of the present invention, the maximum water-cement ratio is 0.4, and the maximum chloride ion content is only 0.10%, which can effectively avoid the corrosion of steel bars. The slag and fly ash are mixed to replace part of the cement, and the slow-setting polycarboxylic acid high-performance water-reducing agent is appropriately added to reduce the water-cement ratio and the amount of cement, while ensuring that it has suitable pumpability and workability.

[0043] During the specific implementation, the water-cement ratio is set first, and the cement consumption without admixture is calculated based on the original water consumption. Then the dosage is considered based on the actual quality of fly ash, iron ore tailings ash and mineral powder. Part of the cement can be replaced in equal amounts. For every cubic meter of concrete, 62.5 kg of S95 grade mineral powder can be used to replace the cement consumption, 81 kg of iron ore tailings ash can be used to replace cement per cubic meter of concrete, and 62.5 kg of fly ash can be used to replace cement per cubic meter of concrete.

[0044] The present invention further provides a method for preparing waterproof and impermeable concrete and its application, comprising the following steps:

[0045] S1, mixing step: firstly, sand, crushed stone, cement, fly ash, iron tailings ash, and mineral powder are sequentially added into the mixer and mixed for a first preset time, then polycarboxylic acid high-performance water reducer, ternary expansion anti-cracking fiber, and nano-hydrated calcium silicate gel are added and mixed with water for a second preset time, and finally, the remaining mixing water is added and mixed for a third preset time to obtain concrete;

[0046] In this step, the two-feeding method is adopted, and the ternary expansion anti-cracking fiber and the polycarboxylic acid high-performance water-reducing agent are dispersed into fiber monofilaments under the action of water immersion and the friction of the mixer, which is beneficial to improve the crack resistance and impermeability of the concrete. The secondary strength of the concrete after using the above nano-hydrated calcium silicate gel, polycarboxylic acid high-performance water-reducing agent and ternary expansion anti-cracking fiber can be increased by about 15%, and cement can be saved by about 15% to 20%.

[0047] Specifically, the first preset time length may be 20-40s, preferably 30s; the second preset time length may be 100-130s, preferably 120s; the third preset time length may be 100-130s, preferably 120s. The total time length of the first preset time length, the second preset time length and the third preset time length is less than or equal to 270s. The particle size of the crushed stone is preferably 5-25mm.

[0048] S2, transportation step: transport the concrete obtained through the above steps to the pouring site for concrete distribution and pouring.

[0049] Specifically, before pouring concrete, clean the base surface. The retention time (initial setting time of concrete) is less than or equal to 45 minutes, and the slump loss is less than or equal to 10%. The total pouring time should not exceed 6 hours, and the longest time should not exceed the initial setting time of concrete.

[0050] S3. Casting and vibrating steps: The concrete wall is cast by inclined layered casting method, and vibrated by a vibrating rod. When using the vibrating rod, it should be straight up and down, inserted quickly and pulled out slowly, and attention should be paid to the position of the steel cage.

[0051] Specifically, in order to avoid concrete segregation during the pouring process, the free pouring height of the concrete must be within 2m. When pouring concrete, the "layered pouring" method is used to simplify the treatment of concrete seepage and ensure that the upper and lower concrete does not exceed the initial setting time.

[0052] The wall concrete is vibrated with a vibrator. When using the vibrator, it should be moved straight up and down, inserted quickly and pulled out slowly. Pay attention to the position of the steel cage. The vibration time for each insertion point is 20 to 30 seconds. Generally, the vibrator is vibrated until the concrete surface no longer sinks significantly and cement slurry appears on the surface.

[0053] S4, a curing step, wherein the concrete is sealed in a formwork and subjected to heat preservation curing for 14 days.

[0054] Specifically, the purpose of sealing concrete is to prevent the poured concrete from being directly exposed to the atmosphere, but to allow it to self-consolidate and harden in a closed space with a smaller temperature difference, so that the concrete admixtures can fully play their role and improve the concrete's own waterproof, anti-corrosion and anti-seepage properties.

[0055] The concrete provided by the present invention is described in detail below with reference to several specific embodiments.

[0056] Embodiment 1:

[0057] Components:

[0058] Water 166.7kg / m 3 、Crushed stone 1056kg / m 3 , sand 760kg / m 3 , cement 271kg / m 3 、Fly ash 62.5kg / m 3 、Iron tailings ash 81kg / m 3 、Mineral powder 62.5kg / m 3 , ternary expansion anti-cracking fiber 0.9kg / m 3 , polycarboxylic acid high performance water reducing agent 5.8kg / m 3 , Nano hydrated calcium silicate gel 36kg / m 3 .

[0059] Preparation method:

[0060] According to the above formula table, sand, crushed stone, cement, fly ash and mineral powder are put into the mixer in turn and mixed for 30 seconds. Then, polycarboxylic acid high-performance water reducer, ternary expansion anti-cracking fiber, nano-hydrated calcium silicate gel mixing water are added and mixed for 120 seconds. Finally, the remaining mixing water is added and mixed for 120 seconds to obtain concrete.

[0061] Comparative Example 1:

[0062] Components:

[0063] Water 166.7kg / m 3 、Crushed stone 1056kg / m 3 , sand 760kg / m 3 , cement 271kg / m 3 、Fly ash 62.5kg / m3 、Mineral powder 62.5kg / m 3 , polycarboxylic acid high performance water reducing agent 5.8kg / m 3 .

[0064] Preparation method:

[0065] According to the above formula table, sand, crushed stone, cement, fly ash and mineral powder are added to the mixer in sequence and mixed for 30 seconds. Then, polycarboxylic acid high-performance water reducing agent and mixing water are added and mixed for 120 seconds. Finally, the remaining mixing water is added and mixed for 120 seconds to obtain concrete.

[0066] Comparative Example 2:

[0067] Components:

[0068] Water 166.7kg / m 3 、Crushed stone 1056kg / m 3 , sand 760kg / m 3 、Cement 271kg / m 3 、Fly ash 62.5kg / m 3 、Iron tailings ash 81kg / m 3 、Mineral powder 62.5kg / m 3 , polycarboxylic acid high performance water reducing agent 5.8kg / m 3 .

[0069] Preparation method:

[0070] According to the above formula, sand, crushed stone, cement, fly ash, iron tailings ash and mineral powder are put into the mixer in sequence and mixed for 30 seconds. Then, polycarboxylic acid high performance water reducing agent and mixing water are added and mixed for 120 seconds. Finally, the remaining mixing water is added and mixed for 120 seconds to obtain concrete.

[0071] Comparative Example 3:

[0072] Components:

[0073] Water 166.7kg / m 3 、Crushed stone 1056kg / m 3 , sand 760kg / m 3 、Cement 271kg / m 3 、Fly ash 62.5kg / m 3 、Mineral powder 62.5kg / m 3 , ternary expansion anti-cracking fiber 0.9kg / m 3 , polycarboxylic acid high performance water reducing agent 5.8kg / m 3 .

[0074] Preparation method:

[0075] According to the above formula table, sand, crushed stone, cement, fly ash and mineral powder are put into the mixer in turn and mixed for 30 seconds. Then, polycarboxylic acid high-performance water reducer and ternary expansion anti-cracking fiber are added and mixed with water for 120 seconds. Finally, the remaining mixing water is added and mixed for 120 seconds to obtain concrete.

[0076] Comparative Example 4:

[0077] Components:

[0078] Water 166.7kg / m 3 、Crushed stone 1056kg / m 3 , sand 760kg / m 3 、Cement 271kg / m 3 、Fly ash 62.5kg / m 3 、Mineral powder 62.5kg / m 3 , polycarboxylic acid high performance water reducing agent 5.8kg / m 3 , Nano hydrated calcium silicate gel 5.42kg / m 3 .

[0079] Preparation method:

[0080] According to the above formula table, sand, crushed stone, cement, fly ash and mineral powder are sequentially added into the mixer and mixed for 30 seconds, then polycarboxylic acid high-performance water reducer and nano-hydrated calcium silicate gel mixing water are added and mixed for 120 seconds, and finally the remaining mixing water is added and mixed for 120 seconds to obtain concrete.

[0081] The concrete in the above-mentioned Example 1 and Comparative Examples 1-4 was subjected to performance tests, and the test results are as follows:

[0082]

[0083] Through experimental comparison, it is found that the concrete in the embodiment of the present invention has better impermeability and waterproofness than the standard concrete. That is to say, after adding the appropriate proportion of iron tailings ash, nano-hydrated calcium silicate gel and polypropylene anti-cracking fiber, the concrete in this embodiment has greatly improved its impermeability and greatly reduced the probability of shrinkage cracks in the concrete. It plays a major role in preventing leakage under high water pressure environment and has a strong guiding role for other similar projects.

[0084] In summary, the above are only preferred embodiments of the present invention and are not intended to limit the protection scope of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A waterproof and impermeable concrete, characterized in that: It is mainly made of the following raw materials: cement 240-300kg / m 3 , Sand 680-850kg / m 3 , Crushed stone 950-1170kg / m 3 、Fly ash 55-70kg / m 3 、Iron tailings ash 72-90kg / m 3 、Mineral powder 55-70kg / m 3 , water reducing agent 5-6.5kg / m 3 , ternary expansion anti-cracking fiber 0.8-1.0kg / m 3 , Nano hydrated calcium silicate gel 30-42kg / m 3 and water 150-185kg / m 3 .

2. The waterproof and impermeable concrete according to claim 1, characterized in that: It is mainly made of the following raw materials: cement 271kg / m 3 , sand 760kg / m 3 、Crushed stone 1056kg / m 3 、Fly ash 62.5kg / m 3 、Iron tailings ash 81kg / m 3 、Mineral powder 62.5kg / m 3 , water reducing agent 5.8kg / m 3 , ternary expansion anti-cracking fiber 0.9kg / m 3 , Nano hydrated calcium silicate gel 36kg / m 3 、Water 166.7kg / m 3 .

3. The waterproof and impermeable concrete according to claim 1, characterized in that: The cement is P·O42.5 silicate cement; the particle size of the sand is 0.25-0.5 mm, and the mud content is less than or equal to 3%; the particle size of the crushed stone is 5-25 mm.

4. The waterproof and impermeable concrete according to claim 1, characterized in that: The fly ash is of grade II, with a fineness of less than 25%, a loss on ignition of less than 8%, and a water requirement ratio of less than 105%.

5. The waterproof and impermeable concrete according to claim 1, characterized in that: The main components of the iron tailings ash include SiO2, Fe2O3, Al2O3, CaO, MgO, and Na2O.

6. The waterproof and impermeable concrete according to claim 1, characterized in that: The ternary expansion anti-cracking fiber is a ternary mixed fiber of steel-PVA-polypropylene, and the mixing ratio is 1:0.7:

1.

7. The method for preparing waterproof and impermeable concrete according to any one of claims 1 to 6, characterized in that: The following steps are involved: The sand, gravel, cement, fly ash, iron tailings ash and mineral powder are sequentially added and mixed for a first preset time, then a water reducer, ternary expansion anti-cracking fiber and nano-hydrated calcium silicate gel are added and mixed with water for a second preset time, and finally the remaining mixing water is added and mixed for a third preset time to obtain the waterproof and impermeable concrete.

8. The method for preparing waterproof and impermeable concrete according to claim 7, characterized in that: In the stirring step, the sum of the three preset time lengths should be less than or equal to 270 seconds.

9. The use of the waterproof and impermeable concrete according to claim 7, characterized in that: The application comprises the following steps: Transportation step: transporting the waterproof and anti-seepage concrete to the pouring site for concrete spreading and pouring; Casting and vibrating steps: casting the concrete wall by using an inclined layered casting method, and vibrating by using a vibrating rod; Curing step: performing thermal insulation curing on the concrete in a closed form.

10. The use of the waterproof and impermeable concrete according to claim 9, characterized in that: In the transportation step, the residence time of the concrete is less than or equal to 45 minutes, the slump loss is less than or equal to 10%, and the total pouring time is less than or equal to 6 hours.

Citation Information

Patent Citations

  • Concrete micro-expansion reinforcing agent, preparation method thereof, concrete and application thereof

    CN112592088A

  • Impervious corrosion-resistant concrete prepared from metallurgical solid waste and preparation method of impervious corrosion-resistant concrete

    CN113636806A

  • High-performance concrete with low shrinkage

    CN113979712A

  • Green iron tailing concrete with high carbonization resistance and preparation method thereof

    CN114573295A

  • Concrete, construction method and landfill leachate treatment system

    CN115010435A